Issues in IS/IT investment evaluation, benefits realisation, and outsourcing in Australian organisations: results from a case study - Lin, Chad; Pervan, Graham (University of Western Australia, 2001)
The issue of expected and actual benefits realised from IS/IT investments has generated a significant amount of debate in the IS/IT literature amongst the researchers, academics, and practitioners. This is as true in Australia as it is in the rest of the developed world. Thus, a detailed program of research into the current Australian practice and processes of IS/IT investment evaluation and benefits realisation was initiated. As part of this research program an in-depth case study of these practices and processes in a large government agency, with a mix of insourced and outsourced IS/IT activities, was conducted. A number of issues have emerged from the analysis of the text data and the key issues are presented below in some detail. These include a lack of a formal IS/IT investment evaluation methodology and a lack of understanding of the evaluation approach used, the use of a formal benefits realisation methodology and a good understanding of benefits management practices, the use of an informal IS/IT investment evaluation process and a focus on quantitative IS/IT investment evaluation measures, conflicting motivations for outsourcing and different perceptions of success of the contracts by stakeholders, an IS/IT skill shortage within the organisation, an embedded contract mentality, lack of user involvement/participation in contract development, conflict between motivation of outsourcing and criteria for determining the success of the outsourcing contracts, general lack of commitment by contractors, restrictive government guidelines, and rigorous benefits realisation process.